Evaluation of longitudinal steroid profiles from male football players in UEFA competitions between 2008 and 2013. Issue 7 (3rd September 2015) - Baume, Norbert; Geyer, Hans; Vouillamoz, Marc; Grisdale, Richard; Earl, Mike; Aguilera, Rodrigo; Cowan, David A.; Ericsson, Magnus; Gmeiner, Günter; Kwiatkowska, Dorota; Kioukia‐Fougia, Nassia; Molina, Adeline; et al.
Abstract : Testosterone and related compounds are the most recurrent doping substances. The steroid profile, consisting of the quantification of testosterone and its metabolites, has been described as the most significant biomarker to detect doping with pseudo‐endogenous anabolic steroids. The steroidal module of the Athlete Biological Passport (ABP) was launched by the World Anti‐Doping Agency (WADA) in 2014. To assess the value of introducing the module to its anti‐doping programme, the Union of European Football Associations (UEFA) decided to analyze retrospectively the steroid profile data of 4195 urine samples, collected from 879 male football players and analyzed in 12 WADA‐accredited laboratories between 2008 and mid‐2013. This study focused on the evaluation of T/E ratios. The coefficient of variation (CV) and the adaptive model were the two statistical models used to study the longitudinal follow‐up. A CV of 46% was determined to be the maximal natural intra‐individual variation of the T/E when the sequence consisted of single data points analyzed in different laboratories. The adaptive model showed some profiles with an atypical T/E sequence and also enabled an estimate of the prevalence of external factors impacting the T/E sequences. Despite the limitations of this retrospective study, it clearly showed that the longitudinal and individual follow‐up of the T/E biomarker of the players is a good tool for target testing in football. UEFA has therefore decided to implement the steroidal module of the ABP from the start of the next European football season in September 2015. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The ABP Steroidal module implemented by the World Anti‐Doping Agency in 2014 was evaluated by the Union of European Football Associations (UEFA) using more than 4000 urine samples collected on over 870 male football players from 2008 to 2013. This retrospective study investigated the individual longitudinal follow‐up of steroid profiles and especially the T/E biomarker analyzed in twelve anti‐doping laboratories. Based on these results, UEFA is going to implement this valuable ABP tool in their anti‐doping program since September 2015.